Prevalence of the metabolic syndrome in Luxembourg according to the Joint Interim Statement definition estimated from the ORISCAV-LUX study - Scheen André; Lair Marie-Lise; Sauvageot Nicolas; Donneau Anne-Françoise; Alkerwi Ala'a; Albert Adelin; Guillaume Michèle (BMC, 2011)
Abstract Background The prevalence of the metabolic syndrome (MS) has been determined in many countries worldwide but never in Luxembourg. This research aimed to 1) establish the gender- and age-specific prevalence of MS and its components in the general adult population of Luxembourg, according to the most recent Joint Interim Statement (JIS) definition, by using both the high and low cut-off points to define abdominal obesity, and 2) compare and assess the degree of agreement with the Revised National Cholesterol Education Programme-Adult Treatment Panel III (R-ATPIII) and the International Diabetes Federation (IDF) definitions. Methods A representative stratified random sample of 1349 European subjects, aged 18-69 years, participated to ORISCAV-LUX survey. Logistic regression and odds ratios (OR) were used to study MS prevalence with respect to gender and age. The Framingham risk score (FRS) to predict the 10-year coronary heart disease (CHD) risk was calculated to compare the proportion of MS cases below or above 20%, according to both high and low waist circumference (WC) thresholds. Cohen's kappa coefficient (κ) was utilized to measure the degree of agreement between MS definitions. Results The prevalence of the MS defined by the JIS was 28.0% and 24.7% when using the low (94/80) and the high (102/88) WC cut-off points, respectively. The prevalence was significantly higher in men than in women (OR = 2.6 and 2.3 for the low and high WC thresholds), as were all components of the MS except abdominal obesity measured by both thresholds. It also increased with age (OR values in age categories ranging from 2.7 to 28 when compared to the younger subjects for low WC and from 3.3 to 31 for the high WC cut-offs). The 10-year predicted risk of CHD by FRS did not depend on the threshold used. Globally, excellent agreement was observed between the three definitions of MS (κ= 0.89), in particular between JIS and IDF (κ = 0.93). Agreement was significantly higher in women than in men, and differed between age groups. Conclusion Regardless of the definition used, the adult population of Luxembourg reveals a high MS prevalence. Our findings contribute to build evidence regarding the definitive construct of the MS, to help selecting the waist circumference thresholds for Europid populations, and to support the need to revise the guidelines for abdominal obesity levels.